Өзбек ҳәм қарақалпақ тили диалектлериниң байланысы (Ю.Ибрагимовтың илимий жумыслары мысалында) - Шынназарова, С.Ж; Кайпназарова, М.К; Гҥлимбетова, Г.Д. Өзбек ҳәм қарақалпақ тили диалектлериниң байланысы (Ю (ILIM hám JÁMIYET, 2021)
The article is devoted to the study of the language of the Uzbek people in the Republic of Karakalpakstan. The main scientific works of professor Yu.M. Ibragimov, the founder of Nukus school of dialectology are considered in the field of dialeсtology. There have been analyzed the examples of Uzbek dialeсts in Karakalpakstan.